Luxatio erecta humeri with neurovascular compromise: inferior glenohumeral dislocation illustrating associated injuries. (8th October 2016) - Owen, David; Nambiar, Mithun; Moore, Peter; Thomas, Malcolm
Abstract : Luxatio erecta humeri (LEH) is a rare type of shoulder dislocation in which the humeral head becomes trapped beneath the glenoid. Patients present with the arm in a fixed hyperabducted position. LEH is estimated to occur in 0.5% of all shoulder dislocations, most often caused by trauma and has a significant association with local bone, ligament and less frequently neurovascular injury. We present a case with initial neurovascular compromise and sustained neurological impairment at long-term follow-up. Urgent closed reduction is advocated and subsequent treatment is dependent on associated injuries.